Aplikasi Akuaponik Sayur Organik-Ikan Lele dalam Ember (Asoileledamber) di Kota Bengkulu - Risky Hadi Wibowo; Sipriyadi Sipriyadi; Nanang Sugianto; Stella Reformanda Sembiring; Margareth Hutasoit; Yuni Kristina Serlyani; Thoriqul Hidayah (Universitas Mathla'ul Anwar Banten, 2020)
AQUAPONIC APPLICATION OF ORGANIC VEGETABLES-CATFISH IN BUCKETS (ASOILELEDAMBER) IN BENGKULU CITY. Bengkulu City is the capital of Bengkulu Province with the highest population in Bengkulu Province so it requires the availability of high food consumption as well. Required foodstuffs such as vegetables, meat, and fish, not all are available from Bengkulu City, so it is not uncommon the price on the market becomes more expensive. To fulfill the needs of foodstuffs, some people of Bengkulu City make effort to cultivate vegetables and maintain fish in ponds, but this method is also difficult to do because of the limited land area. Based on the description, it is necessary to apply the Appropriate Technology (TTG) for the people of Bengkulu City to fulfill family food security, one of which is the application of aquaponic technology: Asoileledamber (Organic Vegetable-Catfish Aquaponics in Buckets). This community service activity aims to provide information and training to the group of service partners in Bengkulu City about the benefits of Asoileledamber. Community service activities include Asoileledamber counseling activities, the provision of guidebooks, provision of tools and materials for cultivation such as fish seedlings, vegetable seeds and pellet feed. The results perceived by the service partners were harvesting Catfish from the second month of maintenance to the fourth month of maintenance. Organic vegetables are harvested starting from 2 weeks after planting time (SMT) until the 4th month of maintenance with an average harvest of 1-2 bunches per bucket.